Advances in Immunomodulatory Mesoporous Silica Nanoparticles for Inflammatory and Cancer Therapies - Bin Gu; Qin Zhao; Yiran Ao (Biomolecules)
In recent decades, immunotherapy has been considered a promising treatment approach. The modulatable enhancement or attenuation of the body’s immune response can effectively suppress tumors. However, challenges persist in clinical applications due to the lack of precision in antigen presentation to immune cells, immune escape mechanisms, and immunotherapy-mediated side effects. As a potential delivery system for drugs and immunomodulators, mesoporous silica has attracted extensive attention recently. Mesoporous silica nanoparticles (MSNs) possess high porosity, a large specific surface area, excellent biocompatibility, and facile surface modifiability, making them suitable as multifunctional carriers in immunotherapy. This article summarizes the latest advancements in the application of MSNs as carriers in cancer immunotherapy, aiming to stimulate further exploration of the immunomodulatory mechanisms and the development of immunotherapeutics based on MSNs.